The antibacterial properties of phenolic isomers, carvacrol and thymol - Kachur, Karina; Suntres, Zacharias (Critical reviews in food science and nutrition, 2020)
Most of the antibacterial activities of essential oils from the Lamiaceae herbaceous plant family thyme and oregano are attributed to their bioactive isomeric monoterpenoid constituents, carvacrol and thymol. Commercially available antibiotics of thymol or carvacrol have not yet been developed but health products have incorporated thymol into their formulations for their antimicrobial properties. Carvacrol and thymol are generally considered safe for consumption and they have been used in dental applications, approved as food flavorings and have been considered as antibacterial additives in food and feed. Many studies have demonstrated that carvacrol and thymol are potent antibacterial agents against both Gram-positive and Gram-negative bacteria. The most frequently reported mechanism of antibacterial action of both isomers involves the disruption of bacterial membrane leading to bacterial lysis and leakage of intracellular contents resulting in death. Other proposed mechanisms of antibacterial action include the inhibition of efflux pumps, prevention in the formation and disruption of preformed biofilms, inhibition of bacterial motility, and inhibition of membrane ATPases. In addition, both isomers have been found to act additively or synergistically with conventional antibiotics important in overcoming the problem of bacteria resistance in food and disease.